2011
DOI: 10.1016/j.socscimed.2011.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood conditions are associated with maternal health behaviors and pregnancy outcomes

Abstract: Women residing in neighborhoods of low socioeconomic status are more likely to experience adverse reproductive outcomes; however, few studies explore which specific neighborhood features are associated with poor maternal health behaviors and pregnancy outcomes. Based upon our conceptual model, directly observed street-level data from four North Carolina US counties were used to create five neighborhood indices: physical incivilities (neighborhood degradation), social spaces (public space for socializing), walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 36 publications
(50 reference statements)
5
97
1
1
Order By: Relevance
“…Analysis of collinearity index of the model show that tolerance index in all variables is less than 0.2 and index of covariance inflation is not also bigger (usually bigger than 10 as a criterion), therefore, collinearity between predictor variables is not tolerable. (18,19,20,21,22,23,24,25,26). According to the reports, the Organization of Health and Human Services of the United States, unhealthy behaviors and lifestyle are two important factors that cause 10 cases of mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of collinearity index of the model show that tolerance index in all variables is less than 0.2 and index of covariance inflation is not also bigger (usually bigger than 10 as a criterion), therefore, collinearity between predictor variables is not tolerable. (18,19,20,21,22,23,24,25,26). According to the reports, the Organization of Health and Human Services of the United States, unhealthy behaviors and lifestyle are two important factors that cause 10 cases of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Wulandari (2011) stated that family support was an important factor during pregnancy (22). Vinikoor-Imler et al (2011) in his study on pregnant women showed that there was a relationship between high level of physical unawareness and harmful consequences of pregnancy; they showed that high level of walking was inversely related to the pressures of pregnancy (23). Roberts et al (2014) conducted a study on the promotion of psychological well-being of women with PKU Fateel during pregnancy and considered psychological support as a key factor for improving psychological well-being during pregnancy (24) In a study on older women, Morovvati Sharifabad et al (2004) concluded that there was a relationship between HPBs and perceived religious support (25).…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Previous studies have reported the negative impact of neighborhood violent crime rate and neighborhood economic disadvantage on pregnancy, breastfeeding, and childhood outcomes, including allostatic load, which is the ''wear and tear'' on the body, potentially leading to increased cardiometabolic risk, in response to chronic actual or perceived stress. 18,28,29,35 While allostatic load has not been directly linked to lactation to our knowledge, it may provide a mechanistic link between neighborhood structural factors and lactation outcomes. Burdette reported an association between neighborhood economic deprivation and lower odds of initiation but not duration of breastfeeding, even after accounting for individual socioeconomic factors in a longitudinal lowincome non-NICU birth cohort.…”
Section: Discussionmentioning
confidence: 99%
“…30 It may be challenging for residents of high-rental neighborhoods to grow place attachment, which may help explain why more rental housing remained associated with active coping, negative partner support, and perceived racism, even after adjustment. Further, considerable research shows that residential characteristics, like vacancy and incivilities (nuisances), are associated with unhealthy behaviors even after adjustment for individual-level confounders 9,24,31 ; similar mechanisms likely contribute to an unhealthy psychosocial profile as well.…”
Section: Discussionmentioning
confidence: 99%
“…1 The built environment, defined here to include the external physical conditions of the home, infrastructures, and resources that are created or modified by people, including schools, workplaces, parks/recreations areas, business areas, and roads, 28 is an important component of the total environment to which women are exposed during pregnancy and has been previously associated with adverse maternal and reproductive health outcomes (Messer et al, manuscript submitted for publication; Miranda et al, manuscript submitted for publication 31 ;). The residential environment is a critical component of the built environment (Miranda et al, manuscript submitted for publication).…”
mentioning
confidence: 99%